Is the Greek Crisis One of Supply or Demand?. - Ioannides, Yannis Menelaos.; Pissarides, Christopher A. (Tufts University. Tisch Library., 2016)
Slides from a presentation given at the Brookings Panels of Economic Activity, Greek Debt Crisis Pane, September 10, 2015.